Linking bioeconomy, circular economy, and sustainability: Trends, gaps and future orientation in the bio-based and biodegradable plastics industry - Eleonora Foschi; Selena Aureli; Angelo Paletta (European Journal of Social Impact and Circular Economy, 2023)
Bio-based and biodegradable plastics (BBPs) are innovative materials, wholly or partially produced from biomass, with the potential to enhance the circulation of resources in the biological cycle of the Ellen MacArthur Foundation’s butterfly diagram. Although BBPs are generally considered more environmental-friendly than conventional plastics, robust scientific evidence is still missing. The lack of tools and metrics to assess the circularity and sustainability of the BBPs industry poses relevant challenges for its upscaling and contribution to climate neutrality goals in Europe. It calls for adopting system and life cycle thinking, guided by multi-level and multi-dimensional examinations, which led researchers to build a comprehensive picture of trends, gaps and future orientations that may boost a sustainable circular bioeconomy in the sector. The value- chain based and multi-faceted SWOT analysis that emerged from the intersection of system and corporate data reveals the need to establish a combined circular bioeconomy strategy where incentives to integrated local supply chain, dedicated EPR scheme, eco-design guidelines, revised EoL standards, new clear labelling schemes and harmonised sustainability criteria should be prioritized and conjointly pursued to accelerate the transition towards a sustainable circular bioeconomy of the BBPs value chain.